2019
DOI: 10.1590/s1984-29612019035
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the distribution of natural Toxoplasma gondii infection among equids in Northeastern Brazil

Abstract: The aim of this study was to determine the frequency and factors associated with Toxoplasma gondii in naturally infected equids in northeastern Brazil. Serum samples from 569 equids (528 horses, 8 mules and 33 donkeys) were subjected to the indirect fluorescent antibody test. Generalized linear models were used to evaluate associated factors. Among the 569 animals sampled, 118 (30.6%) living in rural areas and 14 (26.42%) in urban areas were seropositive (p>0.05). Seropositive animals were observed on 95% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The differences in prevalence may be associated with housing, stable hygiene and feeding practices [ 7 , 41 ]. The prevalence of T. gondii was higher in donkeys (72.7%) than in horses (27.7%) in a recent study from Brazil [ 42 ], as well as in other studies from Spain [ 23 ] and Pakistan [ 43 ]. However, since there are fewer studies evaluating both horses and donkeys in similar cohorts, it is difficult to determine whether these differences reflect a higher susceptibility of donkeys, or merely reflect differences in sanitation or management practices between these species.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The differences in prevalence may be associated with housing, stable hygiene and feeding practices [ 7 , 41 ]. The prevalence of T. gondii was higher in donkeys (72.7%) than in horses (27.7%) in a recent study from Brazil [ 42 ], as well as in other studies from Spain [ 23 ] and Pakistan [ 43 ]. However, since there are fewer studies evaluating both horses and donkeys in similar cohorts, it is difficult to determine whether these differences reflect a higher susceptibility of donkeys, or merely reflect differences in sanitation or management practices between these species.…”
Section: Discussionmentioning
confidence: 79%
“…However, since there are fewer studies evaluating both horses and donkeys in similar cohorts, it is difficult to determine whether these differences reflect a higher susceptibility of donkeys, or merely reflect differences in sanitation or management practices between these species. Since horses are considered to be naturally resistant to T. gondii infection [ 42 ], it is possible that they develop lower antibody titers that are not detected by serological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Age was not a factor associated with infection in horses. In other species studies have shown that age could be is a risk factor, but this generally does not occur with equids (Munhoz et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…The difference in seroprevalence can result from hygiene conditions, managing, and feeding practices (Li et al 2020;Tenter et al 2000). From different countries in the world, different seroprevalence results are reported that the seroprevalence of the parasite is higher in donkeys than in horses; Brazil (Munhoz et al 2019) 72% in donkeys and 27% in horses and parallel, other studies from Pakistan (Saqib et al 2015) and Spain (Garcia-Bocanegra et al 2012) can be suggested. However, because of are fewer studies evaluating both species in the same cohorts, it is di cult to determine that these results are caused by the naturally higher susceptibility of donkeys or poor sanitary conditions.…”
Section: Discussionmentioning
confidence: 96%